2008
DOI: 10.1089/aid.2008.0002
|View full text |Cite
|
Sign up to set email alerts
|

Association between ABO and Rhesus Blood Group Systems among Confirmed Human T Lymphotropic Virus Type 1-Infected Patients in Northeast Iran

Abstract: The distribution of ABO and Rhesus blood group types was investigated in 984 randomly selected human T lymphotropic virus-1(HTLV-1)-infected blood donors from April 2004 to March 2007. A total of 1081 healthy controls admitted for blood donation in this period were enrolled in this study. Infected and control individuals were from the same region and their ABO/Rhesus blood group types were determined by the standard tube test technique. All blood samples were screened for HTLV-1 using an enzyme-linked immunoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…Similarly studies carried out in Enugu by Nneli and colleagues [ 38 ] and in Adamawa State by Abdulazeez and colleagues [ 39 ] indicated that HIV positivity was more predominant among group O subjects. Similarly, a study to investigate the distribution of ABO and Rhesus blood group types in 984 randomly selected human T lymphotropic virus-1(HTLV-1)-infected blood donors observed that donors who are AB+ have increased risk of HTLV-1 infection [ 40 ]. The reason for this predisposition may be genetic or it may also be due to the fact that blood group O is the most prevalent ABO blood groups among blacks and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly studies carried out in Enugu by Nneli and colleagues [ 38 ] and in Adamawa State by Abdulazeez and colleagues [ 39 ] indicated that HIV positivity was more predominant among group O subjects. Similarly, a study to investigate the distribution of ABO and Rhesus blood group types in 984 randomly selected human T lymphotropic virus-1(HTLV-1)-infected blood donors observed that donors who are AB+ have increased risk of HTLV-1 infection [ 40 ]. The reason for this predisposition may be genetic or it may also be due to the fact that blood group O is the most prevalent ABO blood groups among blacks and Caucasians.…”
Section: Discussionmentioning
confidence: 99%
“…Other infectious diseases, such as Chagas’ disease and dengue fever, have a more aggressive and symptomatic course in AB-group individuals [22, 23]. Infection with HTLV-1 has also been more frequently observed in blood group AB [24]. A higher proportion of HIV-infected AB-group individuals could therefore develop symptoms earlier in life, which would consequently exclude them from blood donation.…”
Section: Discussionmentioning
confidence: 99%
“…in subjects of northeast Iran. [20] It is obvious that more attention to quality control programs in blood banking laboratory is necessary especially for determination of weak D positive RBCs and reporting of D negative blood group. Furthermore antibody screening should be performed for Rh (D, C and E) antigens as the most common alloantibodies in all of the patients from the start of transfusion to reduce transfusion complications.…”
Section: Discussionmentioning
confidence: 99%